Utilization of Wungu leaf extract (Graptophyllum pictum (L.) Griff.) in the formulation of spray sunscreen as a halal cosmetic preparation - Amalina, Faidatul; Rahmayanti, Mayu; Syarifuddin, Sadli; Fadilia Aktifa, Ana (Journal of Halal Science and Research, 2024)
Ultraviolet (UV) A and Ultraviolet (UV) B rays can also hurt the skin, and sunscreen helps keep the skin awake. Wungu leaf has some potential for sunscreen because it has antioxidant activity that allows it to absorb UV light. Besides considering the security aspect, the formulation of the sunscreen spray also observes the halal critical points of the ingredients used. This study aims to formulate a more comprehensive sunscreen spray halal extract of wungu leaves with variations in the concentration of glycerin, a humectant. Data collection techniques run through descriptive analysis. This is made with variations in glycerin concentration: 5%, 10%, and 15%. The availability of formulated physical evaluations then included organoleptic tests, homogeneity tests, pH tests, viscosity tests, and test patterns of spraying. According to this study, availability in green, homogenous pH stands at 5.42 – 5.73, viscosity in the 1571 – 1983 cPs, and the targeting pattern at about 3 cm, 5 cm, 10 cm, and 15 cm at 5.67 – 16.6 cm. Therefore, in this study, the conclusion is that the availability of sunscreen spray with variations of glycerin has more physical properties that could be used. The more glycerin is used, the more available viscosity will increase.